FRI0228 Sarilumab Dose Reduction To Manage Laboratory Abnormalities in An Open-Label Extension Study in RA Patients. (15th July 2016) - Genovese, M.C.; Fay, J.; Parrino, J.; Garg, A.; van Hoogstraten, H.; Boddy, A.; Martincova, R.; Graham, N.; Simon, J.; Burmester, G.R.
Abstract : Background: The investigational agent sarilumab is a human monoclonal antibody directed against the interleukin 6 (IL-6) receptor. In the phase 3 MOBILITY (NCT01061736 ) and TARGET (NCT01709578 ) studies, sarilumab (150 or 200 mg subcutaneously every 2 weeks [q2w] + conventional synthetic disease-modifying antirheumatic drugs [csDMARDs]) demonstrated efficacy in adults with active, moderate-to-severe rheumatoid arthritis (RA). 1 Among the most common treatment-emergent adverse events in both studies were infections, neutropenia, injection site reactions, and increased transaminases. Laboratory changes were consistent with IL-6 signaling blockade. Objectives: This analysis examined laboratory changes and treatment continuation after sarilumab dose reduction in EXTEND (NCT01146652 ), an open-label, follow-up study that evaluated long-term safety and efficacy of sarilumab with or without concomitant csDMARDs. Methods: Adults with RA who previously participated in sarilumab studies were eligible. Patients who entered into EXTEND before dose selection for the phase 3 studies received sarilumab 150 mg every week. After dose selection for the phase 3 studies, patients were switched to or initiated on sarilumab 200 mg q2w. Per protocol, investigators could have reduced the dose of sarilumab to 150 mg q2w for absolute neutrophil count (ANC) ≥0.5 to 1.0 Giga/L, platelet count ≥50 to 100 Giga/L, or alanine aminotransferase (ALT) ≥3 to 5× upper limit of normal. Dose reductions to avoid laboratory changes were also performed at the investigator's discretion. Efficacy data from EXTEND were analyzed before and 24 weeks after dose reduction for patients entering from the MOBILITY (n=158) and TARGET (n=42) studies. Results: As of the April 2015 interim analysis, dose reduction from sarilumab 200 to 150 mg q2w had occurred in 15% of patients. The most common reasons for dose reduction were decreases in ANC (9.5%) and elevations in ALT (3.3%) (Table ). Infection was the most common non-laboratory reason for dose reduction (0.4%). At the time of analysis, 80.1% of patients who dose reduced were continuing treatment, with a mean treatment duration of 1.5 years after dose reduction. Improvements in ANC and ALT were observed over the 6 months after dose reduction. Efficacy of sarilumab was maintained in patients from MOBILITY and TARGET after dose reduction in EXTEND as assessed by ACR20 responses (83.3% and 77.4%, respectively) and HAQ-DI scores (-0.68 and -0.73, respectively). Conclusions: In patients whose sarilumab dose was decreased from 200 mg q2w to 150 mg q2w, there was an improvement in laboratory abnormalities and continuation of treatment for the majority of patients. Improvements in signs and symptoms of RA and physical function were maintained after dose reduction. References: Genovese et al. Arthritis Rheumatol. 2015;67:1424–1437. Acknowledgement: This study was sponsored by Sanofi and Regeneron Pharmaceuticals, Inc. Editorial support was provided by Kristi Porter, PhD, MedThink SciCom, and funded by Sanofi and Regeneron Pharmaceuticals, Inc. Disclosure of Interest: M. Genovese Grant/research support from: Roche, Sanofi, GSK, R-Pharma, RuiYi, and Bristol-Myers Squibb, Consultant for: Roche, Sanofi, GSK, R-Pharma, RuiYi, and Bristol-Myers Squibb, J. Fay Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, J. Parrino Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, A. Garg Shareholder of: Sanofi, Employee of: Sanofi, H. van Hoogstraten Shareholder of: Sanofi, Employee of: Sanofi, A. Boddy Shareholder of: Sanofi, Employee of: Sanofi, R. Martincova Shareholder of: Sanofi, Employee of: Sanofi, N. Graham Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, J. Simon: None declared, G. Burmester Grant/research support from: from AbbVie, Bristol-Myers Squibb, MedImmune, Merck, Pfizer, Roche, and UCB, Consultant for: from AbbVie, Bristol-Myers Squibb, MedImmune, Merck, Pfizer, Roche, and UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Merck, Pfizer, Roche, and UCB